Contemporary Muslim Scholars’ Resistance to Misogynistic Interpretations of Women’s Voices in the Qur’an - Ach Badri Amien; Abd A'la; M. Saad AlFanny; Mei Nur Azizah (Al Furqan: Jurnal Ilmu Al Quran dan Tafsir, 2025)
Issues related to women have long been a subject of continuous debate among both men and women. In Islamic discourse, women are often portrayed either as adornments of the world (zinatun) or as sources of temptation (fitnatun). One aspect that receives considerable attention is the perceived seductive nature of women's voices, as referenced in the Qur’an (Q. 33:32). This study adopts a descriptive qualitative method through a library-based approach, drawing from books, journals, classical and contemporary Qur’anic interpretations, and relevant literature. The findings reveal two key insights. First, the Qur’anic advice for women to speak firmly and clearly to non-mahram men aims to prevent misinterpretations stemming from men's susceptibility to sexual temptation. Second, this gendered framing is reflected in interpretations of the story of Yusuf and Zulaikha (Q. 12:28). Scholars such as Thaifur Ali Wafa and M. Quraish Shihab argue that temptation is not inherently rooted in women, but rather in passive male attitudes that often portray themselves as victims. Consequently, interpretations that link women's voices to moral weakness reflect patriarchal cultural constructs that must be critically reassessed. A more contextual, gender-sensitive hermeneutic is needed to challenge misogynistic readings of the Qur’an and to promote justice and dignity for women within Islamic discourse.